Genomic evidence supports the introgression between two sympatric stickleback species inhabiting the White Sea basin - Nedoluzhko, Artem; Sharko, Fedor; Tsygankova, Svetlana; Boulygina, Eugenia; Ibragimova, Amina; Teslyuk, Anton; Galindo-Villegas, Jorge; Rastorguev, Sergey (Heliyon, 2021)
publishedVersion Unit License Agreement